Antibacterial synergy between rutin and florfenicol enhances therapeutic spectrum against drug resistant Aeromonas hydrophila. (October 2019) - Deepika, Murugesan Sathiya; Thangam, Ramar; Vijayakumar, Tharumasivam Siva; Sasirekha, Rajendran; Vimala, R.T.V.; Sivasubramanian, Srinivasan; Arun, Sridhar; Babu, Manikandan Dinesh; Thirumurugan, Ramasamy
Abstract: Emergence of antibiotic resistant bacteria has necessitated the drive to explore competent antimicrobial agents or to develop novel formulations to treat infections including Aeromonas hydrophila . The present study investigates the synergistic antibacterial effects of citrus flavonoid rutin and florfenicol (FF) against A. hydrophila in vitro and in vivo . Rutin is extracted and purified from Citrus sinensis peel through preparative HPLC and characterized through TLC, GC-MS and 1 H and 13 C NMR analyses. Though rutin did not display significant antibacterial activity, it modulated FF activity resulting in four-fold reduction in the MIC value for FF. The anti-biofilm potential of synergistic association of rutin and FF was validated by protein analysis, quantification of exopolysaccharide (EPS) and microscopy studies using sub-MIC doses. Besides antibacterial action, in vivo studies showed that Rutin/FF combination enhanced host immunity by improving blood cell count, anti-protease, and lysozyme activities as well as decreased the oxidative stress and the pathological changes of tilapia Oreochromis niloticus against A. hydrophila infection. No significant DNA damages or clastogenic effects were detected in tilapia challenged with A. hydrophila under Rutin/FF treatment. It is shown that an acute-phase Lipopolysaccharide binding protein (LBP) enhances the innate host defence against bacterial challenge. Semi quantitative RT-PCR and western blot results revealed the significant increase of LBP in the supernatant of tilapia monocytes/macrophages challenged with A. hydrophila upon treatment. The study findings substantiate that the combination of natural molecules with antibiotics may open up possibilities to treat MDR strains. Graphical abstract: Image 1 Highlights: Combination of Rutin and FF exhibited synergistic anti -biofilm potential against MDR A. hydrophila at their sub-MIC level. Rutin/FF revealed the enhanced immunomodulatory activity against A. hydrophila. Rutin/FF reduced the virulence of bacterium by enhancing host immunity, decreasing oxidative stress and genotoxic effects. Rutin/FF reduced the pathological changes of tilapia infected with A. hydrophila. Rutin/FF provoked the expression of lipopolysaccharide binding protein (LBP) in tilapia against A. hydrophila.